Describing the Indescribable: Repressive Regime and Discourse Productivity in Jekyll and Hyde - M. Irfan Zamzami (English Letters Department, Faculty of Letters, Universitas Sanata Dharma, 2026)
This paper investigates the paradox of language and repression in Strange Case of Dr Jekyll and Mr Hyde, focusing on how the narrative persistently avoids describing Edward Hyde in precise, objective terms. Despite Hyde’s centrality to the plot, characters repeatedly fail or refuse to articulate his physical appearance. Drawing on Michel Foucault’s “repressive hypothesis,” the study argues that the narrative’s avoidance of descriptive language constitutes a form of discursive repression, a regime that limits what can be said, yet paradoxically stimulates more discourse. Using close textual analysis grounded in narratology and Foucauldian theory, the paper identifies a formal pattern in which descriptions of Hyde emerge only in vague, affective terms followed immediately by disavowal or narrative deferral. These moments of muteness and subsequent verbal excess suggest that repression does not silence but incites discourse. The study further argues that this dynamic is not a narrative flaw but a structural feature serving both the detective and gothic genre conventions. The repression of descriptive language sustains suspense while reinforcing thematic concerns about the limits of rationality and the boundaries of the knowable self. Ultimately, Hyde’s indescribability is not a gap in the story but the engine of its discourse. His mystery is not maintained by silence, but by the repeated failure to describe him.